Post-discharge persistent symptoms and health-related quality of life after hospitalization for COVID-19. Issue 6 (December 2020) - Garrigues, Eve; Janvier, Paul; Kherabi, Yousra; Le Bot, Audrey; Hamon, Antoine; Gouze, Hélène; Doucet, Lucile; Berkani, Sabryne; Oliosi, Emma; Mallart, Elise; Corre, Félix; Zarrouk, Virginie; et al.
Abstract: Objective: To assess post-discharge persistent symptoms and health-related quality of life (HRQoL) of patients hospitalized in a COVID-19 ward unit more than 100 days after their admission. Methods: All eligible patients were contacted by phone by trained physicians and were asked to answer to a dedicated questionnaire. Patients managed in hospital ward without needing intensive care were compared with those who were transferred in intensive care units (ICU). Results: We included 120 patients after a mean (±SD) of 110.9 (±11.1) days following admission. The most frequently reported persistent symptoms were fatigue (55%), dyspnoea (42%), loss of memory (34%), concentration and sleep disorders (28% and 30.8%, respectively). Comparisons between ward- and ICU patients led to no statistically significant differences regarding those symptoms. In both group, EQ-5D (mobility, self-care, pain, anxiety or depression, usual activity) was altered with a slight difference in pain in the ICU group. Conclusion: Most patients requiring hospitalization for COVID-19 still have persistent symptoms. While there were few differences between HRQoL between ward and ICU patients, our findings must be confirmed in larger cohorts, including more severe patients.